2012
DOI: 10.1100/2012/625731
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Nitrogen Use Efficiency with the Activities of Enzymes Involved in Nitrogen Uptake and Assimilation of Finger Millet Genotypes Grown under Different Nitrogen Inputs

Abstract: Nitrogen responsiveness of three-finger millet genotypes (differing in their seed coat colour) PRM-1 (brown), PRM-701 (golden), and PRM-801 (white) grown under different nitrogen doses was determined by analyzing the growth, yield parameters and activities of nitrate reductase (NR), glutamine synthetase (GS), glutamate synthase; GOGAT, and glutamate dehydrogenase (GDH) at different developmental stages. High nitrogen use efficiency and nitrogen utilization efficiency were observed in PRM-1 genotype, whereas hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
47
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 36 publications
10
47
0
Order By: Relevance
“…Genotypic variability among different finger millet cultivars has been reported for responsiveness to N and P [54]. Gupta et al [6] ) under pot conditions. They found that there was genotypic variability among the finger millet genotypes' responses to different N inputs, wherein some varieties were highly responsive to N. Therefore, identification of genotypes with higher N use efficiency and N utilization efficiency especially under low available soil N levels will benefit farmers who cannot afford N fertilizer or who do not have access to N fertilizer sources.…”
Section: Varietal Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Genotypic variability among different finger millet cultivars has been reported for responsiveness to N and P [54]. Gupta et al [6] ) under pot conditions. They found that there was genotypic variability among the finger millet genotypes' responses to different N inputs, wherein some varieties were highly responsive to N. Therefore, identification of genotypes with higher N use efficiency and N utilization efficiency especially under low available soil N levels will benefit farmers who cannot afford N fertilizer or who do not have access to N fertilizer sources.…”
Section: Varietal Effectsmentioning
confidence: 99%
“…Finger millet responds well to N application [6,22,50], since many of the soils in the semi-arid regions of Asia are deficient in N [25]. Studies concerning N management in finger millet are mainly focused on the amount of N applied, timing of application, and varietal responses to N. Rao et al [51] reported increases in yield and grain protein content in finger millet due to N fertilizer application rates of up to 40 kg N ha −1 in Andhra Pradesh, India.…”
Section: Nitrogen (N)mentioning
confidence: 99%
“…However, excessive N fertilization in cultivated land has profound environmental impacts such as nitrate leaching, soil denitrification, ammonia volatilization, and nitrous oxide emissions, which contaminate water and air and aggravate the climate change [4,5]. While N losses cannot be avoided completely, they can be substantially reduced with sustainable agricultural practice such as adjusting N rate, timing and using the most appropriate fertilizer source, and adopting precision nutrient management technologies [6].…”
Section: Introductionmentioning
confidence: 99%
“…Dida et al, (2008) reported that the crop was domesticated in the highlands of Ethiopia and Uganda 5000 years ago, but reached India 3000 years ago. Today, the crop is ranked fourth globally in importance among the millets, after sorghum, pearl millet, and foxtail millet (Gupta et al, 2012). In India, finger millet is primarily grown in the states of Karnataka, Andhra Pradesh, Odisha, and Tamil Nadu (Dass et al, 2013).…”
Section: Introductionmentioning
confidence: 99%